Mechanical properties of compress stabilised laterite interlocking block using recycled laterite block - Wan Muhammad Zaki , W Abdullah (2014)
Interlocking blocks are known to be an alternative building material used as a structural member like column and wall that can replace the use of conventional building materials such as concrete block and fired clay brick. The usage of recycled waste interlocking block is a possible solution that overall will reduce the materials and construction cost (Raheem, 2012). The aim of this study is to investigate the engineering properties of the recycled waste usage to produce the interlocking block using different percentage of natural fine aggregate and recycled aggregate ( 33.33% and 66.67%). There are 3 types of different curing sets. The result from curing set 1A# (14 days wet in sun) show the highest compressive strength (2.94Mpa) of 28 days curing. This curing method will be used in recycled sets experiment. The result for interlocking block using orange recycled laterite block (5.55Mpa) show a higher compressive strength than curing set 1A# (2.95Mpa) for 28 days. Water absorption for 33.33% recycled interlocking block shows lower percentage than 66.67% recycled interlocking block although the difference just a small value. The block also durable from any working condition and harsh environment as it is proven from abrasion test, the good block is under 6.9% material abraded (Raheem, 2012). Recycled block only loss lesser than 2% of weight after being abraded.